Knowledge about alcohol and alcoholism in a selected group of young people - preliminary - Małgorzata Kardyś; Marianna Charzyńska-Gula; Natalia Klimek-Banaczyk; Marzena Plis (Kazimierz Wielki University, 2018)
Summary Among the many psychoactive substances, which can lead to dependence, particularly important place in the life and customs of youth is alcohol. Young people are particularly susceptible to the harmful use of alcohol primarily because of a lack of knowledge of experience in its consumption. Research has shown that young people under the influence of alcohol more often than others are involved in fights, quarrels, they have a higher risk of falling into conflicts with the police or the law. Increasingly, alcohol became one of the most serious problems in teenage peer environment. The aim of the study was to assess the knowledge about alcohol and alcoholism in a selected group of young people. Used diagnostic survey questionnaire of copyright. They studied 120 students of secondary schools and secondary schools in Tarnobrzeg.The present study indicates ownThat the students showed a greater knowledge of the subject of alcohol, than alcoholism. There is therefore a need for health education and secondary school youth about the consequences of alcohol abuse.